The effect of three different methods applied during peripheral vascular access in prematures on pain and comfort levels - Çiftci, Kamile; Yayan, E.H. (W.B. Saunders, 2022)
Purpose: This research was carried out to determine the influence of kangaroo care, fetal position, and swaddling on pain and comfort levels in preterm infants during peripheral vascular access. Design and methods: The study was conducted as a randomized experimental study with a control group. It included 148 premature infants (kangaroo group = 37, swaddling group = 37, fetal position = 37, control group = 37) of 32–37 weeks of age who had peripheral vascular access in the NICU of a state hospital in eastern Turkey between December 2019 and June 2020. While the infants in the experimental group received kangaroo care, fetal position, and swaddling procedures during and after peripheral vascular access, the infants in the control group received conventional peripheral vascular access without extra intervention. “Newborn Infant Pain Scale (NIPS)” and “Premature Infant Comfort Scale (PICS)” were used to collect data. Data were analyzed using percentile, chi-square and ANOVA tests. Results: Further analysis revealed that the fetal position was the most beneficial intervention for reducing NIPS scores and boosting PICS scores during and after peripheral vascular access in the experimental groups, followed by kangaroo care and lastly swaddling. Conclusion: It was discovered that kangaroo care, fetal position, and swaddling were useful in lowering discomfort and boosting comfort levels in premature infants during and after peripheral vascular access. Practice implications: Kangaroo care, fetal position and swaddling methods can be used in clinical practice in order to reduce the pain level and increase the comfort level during and after peripheral vascular access in prematures. © 2022 Elsevier Inc.
Keywords: Comfort; Fetal position; Kangaroo care; Pain; Peripheral vascular access; Swaddling